Molecular and Genetic Analysis of the Increased Number of Genes for Trypanosoma cruzi Microtubule Associated Proteins in the Class Kinetoplastida - Martin A. Winkler; Alfred A. Pan (Pathogens)
Trypanosoma cruzi GenBank® M21331 encodes for Antigen 36 (Ag 36), which is a tandemly repeated T. cruzi antigen. GenBank M21331 has a gene sequence similarity to human immune genes IFN-α, IFN-β, and IFN-γ, as well as to human TRIM genes. A BLAST-p search revealed that T. cruzi GenBank M21331 had seven gene sequences homologous to microtubule-associated protein (MAP) genes with a 100% amino acid sequence identity. There are 36 genes in the T. cruzi genome with >94% identity to GenBank M21331, and these genes encode proteins ranging in size from 38 to 2011 amino acids in length, the largest containing 20, 25, and 30 repeats of the Ag 36 thirty-eight-amino-acid-sequence motif. The purpose of this study was to perform a genetic and molecular comparative analysis of T. cruzi GenBank M21331 to determine if this gene sequence is unique to the T. cruzi clade, present in the T. brucei clade, and/or exists in other trypanosomatids. There are seven homologous genes to GenBank M21331 in T. cruzi, but only one homolog found of this gene in T. brucei. The MAP genes in T. cruzi appear to have expanded at least eleven-fold in number compared to similar MAP genes in T. brucei. The DNA sequences and functions of these MAP genes in their respective species and clades will be discussed and are a fascinating area for further scientific study.